From the FEC to the Ballot Box: Voter Accountability for Campaign Finance Law Violations. Issue 5 (September 2019) - Gaskins, Ben; Seljan, Ellen; Lochner, Todd; Kowal, Katie; Dundon, Zane; Gold, Maya
Scholarship suggests the Federal Election Commission lacks adequate enforcement tools to deter those who would violate campaign finance laws. But can and do voters hold political candidates accountable for violating these laws? In this article, we employ two studies to empirically evaluate these questions. The first examines the extent to which media cover campaign finance violations, and how they do so. The second employs an experimental approach to test the effects of such media coverage on evaluations of political candidates, in particular whether knowledge of a candidate's violation of campaign finance laws erodes voter support. We find that the media are more likely to cover campaign finance impropriety for high-profile offices, when criminal action is alleged, and for most serious violations. We also show that voters care about campaign violations, and certain violations lower voter support similar to other types of political scandal.